2012
DOI: 10.1134/s0023158412020152
|View full text |Cite
|
Sign up to set email alerts
|

Structure sensitivity of selective acetylene hydrogenation over the catalysts with shape-controlled palladium nanoparticles

Abstract: The structure sensitivity of acetylene hydrogenation on catalysts with controlled shape of palla dium nanoparticles was studied. Palladium particles of cubic (Pd cub ), cuboctahedral (Pd co ) and octahedral (Pd oct ) shapes were obtained by a colloidal method. Poly(N vinyl)pyrrolidone (PVP) was used as the stabi lizer of colloidal solutions. In order to eliminate the effect of the polymer on the properties of the catalyst, PVP was removed from the surface of the particles after their transfer to the support by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…Catalyst testing under non-competitive conditions indicated that particle shape had no impact on selectivity ( Fig. 2) at an equivalent degree of conversion [29]. However, results indicated that turnover frequency (TOF) increased in the order cubes < cuboctahedra < octahedra implying that (111) faces are more active than (100) faces (note: different particle size).…”
Section: Shaped Pd Nanoparticlesmentioning
confidence: 97%
See 2 more Smart Citations
“…Catalyst testing under non-competitive conditions indicated that particle shape had no impact on selectivity ( Fig. 2) at an equivalent degree of conversion [29]. However, results indicated that turnover frequency (TOF) increased in the order cubes < cuboctahedra < octahedra implying that (111) faces are more active than (100) faces (note: different particle size).…”
Section: Shaped Pd Nanoparticlesmentioning
confidence: 97%
“…Similarly, it is important to acknowledge that activity may vary with particle size therefore comparing activity of different particle shapes and sizes may, on occasion, lead to misleading results. Yarulin et al [29] systematically studied the influence of Pd particle shape on acetylene hydrogenation by preparing well defined Pd cubes [(100) faces], cuboctahedra [(100) and (111) faces] and octahedra [(111) faces]. The different morphologies were cleaned using UV light/ozone which has been shown to be an effective way to remove surface residues without altering particle shape [30] -therefore eliminating one potential source of influence from the study.…”
Section: Shaped Pd Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The effects of shape, however, have been far less addressed. Although there are several theoretical studies of acetylene hydrogenation on single planes,4, 6 there are only a handful of experimental results dealing with real catalysts, where the TOF was found to depend on the crystallographic plane exposed, showing activities Pd(1 1 1)>Pd(1 0 0),5c or correlating the catalytic response to the number of crystal boundaries present in a Pd nanowire 7…”
mentioning
confidence: 99%
“…The nature of alumina phases have been very poorly understood in catalysis because of their lower crystallinity [7]. Catalytic performance of alumina supports depends upon the alumina structure, and its active site interactions may be considered in terms of adsorption strength, particle charging and sizes, formation of multi-functional active sites, changes in particle morphology, and dispersion of active sites [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%